A study of the association between UGT1A1*28 variant allele of UGT1A1 gene and colonic phenotype of sporadic colorectal cancer. Issue 4 (April 2019) - Anon, Benjamin; Perray, Clémence; Regnault, David; Caulet, Morgane; Orain, Isabelle; Godart, Bruno; Pages, Jean-Christophe; Tallet, Anne; Ouaissi, Mehdi; Guyetant, Serge; Barin-le Guellec, Chantal; Lecomte, Thierry
Abstract: Introduction: The transcriptional activity of the UGT1A1 gene is modulated by a variable number of repetitions of the dinucleotide (TA) within its promoter region. By comparison to the most common allele (TA)6 (UGT1A1*1), decreased activity is observed with increasing TA repetitions. The aim of this study was to determine whether the presence of the variant allele UGT1A1*28, harbouring seven TA repetitions, (TA)7, in the homozygous state, is associated with precancerous colonic lesions and/or with specific colorectal cancer characteristics. Material and methods: All patients treated for colorectal cancer in a tertiary care centre, between January 2009 and December 2013, who had routine UGT1A1 genotyping for irinotecan dose-adjustment were included. Data were retrospectively collected. Results: 292 patients were enrolled, including 23 UGT1A1 *28/*28 homozygous (7.9%), 137 wild type homozygous (46.9%) and 132 heterozygous (45.2%). There were no significant differences in phenotypic colonic characteristics between homozygous and heterozygous patients carrying the UGT1A1*28 allele as compared to *1/*1 homozygous. Patients treated with aspirin were significantly more common in the UGT1A1 *28/*28 homozygous group than in the other groups (7/23 (30.4%) compared to 22/269 (8.2%), p = 0.001). Conclusion: Dinucleotide polymorphism in the promoter region of the UGT1A1 gene is not associated with a specific colonic phenotype in patients with sporadic colorectal cancer.